Viewing America's energy future in three dimensions - Hegedus, L. Louis; Temple, Dorota S. (RTI Press Publication, 2011)
The future of the US energy infrastructure is a major and urgent challenge for our society. This monograph was stimulated by a report of the National Academies' Committee on America's Energy Future, America's Energy Future: Technology and Transformation, Summary Edition, 2009. The report pointed out the critical but poorly understood and little explored role of societal considerations in determining the fate of national energy policies and programs. In our efforts to respond to those concerns, we have examined the thesis that the three major dimensions of the energy challenge-technology, economics, and societal-are overlapping, interactive, and inseparable; therefore, they can be understood only when considered simultaneously and discussed in terms of their interactions. Correspondingly, this monograph describes energy technologies in the context of their economic and societal contexts, energy economics in their technological and societal contexts, and the societal aspects of energy in their technological and economic contexts. The monograph then identifies social science-driven research opportunities pertaining to America's energy challenge, with the hope that the proposed research will help not only overcome the societal barriers identified by the National Academies' report, but also harness societal forces in developing a rational energy future.